Age Estimation of Adults Using Permanent Mandibular First Molars on Digital Panoramic Radiographs - Meghana Maruthi; Karthikeya Patil; Mahima VG; Nagabhushana Doggalli; Sanjay CJ; Mahesh KP (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: Morphometric analysis of teeth on radiographs for age estimation are considered to be simple, reliable and non-invasive. The aim of this study was to analyse the efficacy of tooth coronal index (TCI) to estimate age in Indian population and to assess the influence of diet and masticatory habit on TCI. The study comprised of 160 subjects in the age range of 21-71 years, categorized into groups based on chronological age, gender, diet and masticatory habit. Coronal Height (CH) and Coronal Pulp Cavity Height (CPCH) of permanent mandibular first molars was measured on digital panoramic radiographs using Planmeca Romexis software measurement tools. TCI was calculated using the formula: TCI= (CPCH ×100)/CH. Statistical analysis was performed, ANOVA and Pearson correlation was applied along with regression analysis to obtain an estimated age using TCI. Results: A negative correlation was obtained between the chronological age and TCI. Three-way ANOVA exhibited a significant difference in TCI within the age groups and dietary groups (p value = <0.05). There was no significant difference within the sexes, sides and masticatory groups. The most precise estimated age using the regression formula was in individuals between 31 – 40 years with an error of +/- 5 years in 55% of females, 65% of males. Conclusions: This study suggests that although TCI is a good predictor of age, it is most suitable to determine age of individuals between 31-40 years with the least error in estimation. This study also throws a light on the influence of diet on TCI.